ANALISIS SOAL DAN KEMAMPUAN PESERTA DIDIK BERBASIS ASESMEN KOMPETENSI MINIMUM PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD ASHFIYA KOTA BANDUNG - Juwita, Sri; Safwannur, Safwannur; Nasir, Tatang Muh; Hajrah, Hajrah; Sidik, Moch. (Attadib: Journal of Elementary Education, 2023)
This study aims to determine the quality of the items on the minimum competency assessment type questions in Islamic Religious Education lessons and to determine the extent to which students' cognitive abilities in solving questions with the AKM type. This type of research is quantitative by displaying numbers and graphics to obtain information. Data processing in this study used the SPSS 26 program and Microsoft Excel. As for the samples in the study, there were 23 students in class IV A at Ashfiya Elementary School, Bandung City. The data sources for this research are questions and results of the Year End Assessment (PAT) for class IV for the 2021/2022 academic year. This study obtained the results that the quality of the AKM type of Islamic Religious Education items consisted of 60% valid questions and 40% invalid questions. The reliability level of the 20 questions obtained very strong results, while the difficulty level did not meet the ideal proportions and there were two questions with very low differentiating power. The cognitive level contained in the AKM type Islamic Religious Education questions in grade IV SD contains the C1-C4 domain. Questions with cognitive level C3 dominate, followed by C4, C2 and C1. When viewed from the cognitive level, the ability of students to solve AKM type Islamic Religious Education questions is very strong in terms of knowledge, understanding aspects are in the good category and the realm of application and analysis is in the sufficient category. So that in making AKM type questions it is necessary to pay attention to the provisions for making questions. As for students' critical thinking skills, they must be re-evaluated in order to improve the quality of educationTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//